2021
DOI: 10.7554/elife.66749
|View full text |Cite
|
Sign up to set email alerts
|

Murine muscle stem cell response to perturbations of the neuromuscular junction are attenuated with aging

Abstract: During aging and neuromuscular diseases, there is a progressive loss of skeletal muscle volume and function impacting mobility and quality of life. Muscle loss is often associated with denervation and a loss of resident muscle stem cells (satellite cells or MuSCs), however, the relationship between MuSCs and innervation has not been established. Herein, we administered severe neuromuscular trauma to a transgenic murine model that permits MuSC lineage tracing. We show that a subset of MuSCs specifically engraft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 95 publications
(124 reference statements)
0
24
1
Order By: Relevance
“…It is possible that disruption of such communication via improper regulation of MuSC protrusions could contribute to the incomplete regeneration seen in diseased muscles ( 58 ). Future investigation of additional intrinsic and extrinsic regulators or other sensors that could be responsible for preserving MuSC protrusions, in combination with extracellular matrices that mimic the living architectural muscle cues ( 59 ) and retain cell-matrix interactions, including nerve injuries that were recently shown to affect MuSC morphology ( 60 ), would allow direct assessment of the essential communication between MuSC states, the niche, and the surrounding environment, including the neuromuscular and myotendinous junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that disruption of such communication via improper regulation of MuSC protrusions could contribute to the incomplete regeneration seen in diseased muscles ( 58 ). Future investigation of additional intrinsic and extrinsic regulators or other sensors that could be responsible for preserving MuSC protrusions, in combination with extracellular matrices that mimic the living architectural muscle cues ( 59 ) and retain cell-matrix interactions, including nerve injuries that were recently shown to affect MuSC morphology ( 60 ), would allow direct assessment of the essential communication between MuSC states, the niche, and the surrounding environment, including the neuromuscular and myotendinous junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the effects of such a treatment on MuSCs and whether additional boosts or different doses might be necessary to maintain MuSC morphology and function in dystrophic muscles over a longer period of time remain to be tested. Moreover, Piezo1 is a bona fide mechanosensitive channel that mediates Ca 2+ signaling in various cell types ( 25 27 , 39 , 60 , 65 ). Thus, we cannot exclude that microenvironmental changes in other muscle cells and/or myofibers may also influence MuSC function and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism remains less clear. On the other hand, MuSCs also actively contribute to the regeneration of neuromuscular junctions in response to denervation [22][23][24]. Therefore, a better understanding of the mechanisms underlying muscle regeneration and MuSC functions is warranted to develop muscle stem cell-based regenerative therapies for both aging and disease conditions.…”
Section: Overviewmentioning
confidence: 99%
“…2017; Larouche et al . 2021) and that depletion of satellite cells dampens the regeneration of NMJs following nerve damage (Liu et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Maladaptation of the muscle is evident during persistent overload in the absence of satellite cells, such as increased extracellular matrix and fibroblast number, indicating a regulatory role for satellite cells in ameliorating unfavourable remodelling of the muscle environment (Murach et al 2018). In relation to the NMJ, it has been shown that a subgroup of satellite cells generate and maintain the specialized myonuclei at the NMJ (Liu et al 2017;Larouche et al 2021) and that depletion of satellite cells dampens the regeneration of NMJs following nerve damage (Liu et al 2015). Although not completely depleted, the aged human muscle has been shown to have fewer satellite cells, especially those associated with type II fibres (Verdijk et al 2007(Verdijk et al , 2014Karlsen et al 2019Karlsen et al , 2020.…”
Section: Introductionmentioning
confidence: 99%